Action-related information trumps system information: Influencing consumers' intention to reduce food waste. (10th July 2020) - Neubig, Christina M.; Vranken, Liesbet; Roosen, Jutta; Grasso, Simona; Hieke, Sophie; Knoepfle, Sandra; Macready, Anna L.; Masento, Natalie A.
Abstract: In order to substantially reduce food waste at the household level, it is essential to change consumer behavior. Informing consumers about the food waste issue is a promising means of bringing about behavior change: research confirms that information can increase food waste reduction behavior. However, it has yet to be determined what kind of information is most effective and exactly how that information affects consumer food waste behavior. This study compares the effects of system vs. action-related information (i.e., knowing what impacts specific actions entail vs. knowing how specific actions can help to accomplish a goal) on behavioral intention towards food waste. That is, the study focuses on the effect of information on the role of food waste in the food system versus information on actions that can be taken to avoid it. Moreover, an adapted model of the Theory of Planned Behavior is used to assess how these information effects are mediated by consumers' attitude, norms, and perceived behavioral control. Results from an online experiment with a between-subjects design (N = 2248) show that action-related information significantly increases respondents' intention to reduce food waste while system information has no significant effect. The change in behavioral intention in the action-related information group is ascribed to greater personal norm activation, more favorable attitudes towards food waste reduction, and higher perceived behavioral control of food waste behaviors. Even though system information does not significantly increase intention to reduce food waste, it results in more favorable attitudes towards food waste reduction. The findings provide insights for policy makers and NGOs on what type of information to consider when designing effective food waste reduction campaigns targeted at consumers, with action-related information supporting the opportunity for consumer behavior change. Highlights: Providing information increases consumers' intention to reduce food waste. Informing consumers about possible actions to reduce food waste is effective. Informing consumers about food waste impacts is not effective in changing intention.